Advances in Carbon Nanostructures - Silva, Adrian M.T; Carabineiro, Sonia A.C (IntechOpen, 2016)
Carbon atoms have the amazing ability to bond in remarkable different manners that can assume distinct astonishing dimensional arrangements from which absolutely diverse and interesting nanostructured carbon materials are obtained. This book aims to cover the most recent advances in (i) Graphene and derivatives, including graphene-based magnetic composites, membranes, wafer devices, and nanofibers for several applications, as well as some particular properties, such as light emission from graphene; (ii) Carbon nanotubes heaters and fibers for reinforcement of cement and diamond-based thin films; and (iii) Nanofluids consisting of both graphene and carbon nanotubes, apart from reporting some important case studies dealing with carbon nanostructures and their use in sensors, coatings, or electromagnetic wave absorbers.